2015
DOI: 10.2527/jas.2014-8771
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zilpaterol hydrochloride on growth performance, blood metabolites, and fatty acid profiles of plasma and adipose tissue in finishing steers1

Abstract: The effects of zilpaterol hydrochloride (ZH) on blood metabolites and fatty acid profiles of plasma and adipose tissue were evaluated in crossbred finishing steers (n = 18, BW 639 ± 12.69 kg) that were stratified by BW and randomly assigned, within strata (block), to receive 0 (control) or 8.33 mg/kg diet DM ZH. Cattle were fed once daily ad libitum in individual feeding pens (9 pens/treatment). Zilpaterol hydrochloride was fed for 23 d and withdrawn 3 d before harvest. Blood samples and measures of BW were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
8
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
7
8
2
2
Order By: Relevance
“…The marked increase in serum BHBA by day 130, and the elevated glucose concentration on days 90 and 130 regardless of treatment may be indicative of an age‐dependent mechanism to secure more readily available energy substrates for body tissues. In accordance with our results, Van Bibber‐Krueger, Miller, Parsons, Thompson, and Drouillard () showed that blood BHBA increased in finishing steers from day 0 to day 21, while another study observed that plasma glucose was higher in finishing steers on day 94 compared with day 49 (Van Bibber‐Krueger, Axman, Gonzalez, Vahl, & Drouillard, ). The increase in BHBA might have been associated with increased epithelial ketogenesis and ruminal volatile fatty acid (VFA) biosynthesis (Naeem, Drackley, Stamey, & Loor, ; Penner, Steele, Aschenbach, & McBride, ).…”
Section: Discussionsupporting
confidence: 92%
“…The marked increase in serum BHBA by day 130, and the elevated glucose concentration on days 90 and 130 regardless of treatment may be indicative of an age‐dependent mechanism to secure more readily available energy substrates for body tissues. In accordance with our results, Van Bibber‐Krueger, Miller, Parsons, Thompson, and Drouillard () showed that blood BHBA increased in finishing steers from day 0 to day 21, while another study observed that plasma glucose was higher in finishing steers on day 94 compared with day 49 (Van Bibber‐Krueger, Axman, Gonzalez, Vahl, & Drouillard, ). The increase in BHBA might have been associated with increased epithelial ketogenesis and ruminal volatile fatty acid (VFA) biosynthesis (Naeem, Drackley, Stamey, & Loor, ; Penner, Steele, Aschenbach, & McBride, ).…”
Section: Discussionsupporting
confidence: 92%
“…These results using clen buterol are in contrast to the present experiment where wholeblood glucose was decreased by feeding ZH and it was less after vs. before feeding ZH. However, the current data are similar to other data from an experi ment using ZH (Van BibberKrueger et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…The increase was temporary as after 9 d of clenbuterol feeding, glucose concentrations were not different (Eisemann et al, 1988). It was hypothe sized by the authors that the initial spike in glucose was caused by elevated liver gluconeogensis or glycoge nolysis (Eisemann et al, 1988), but then cells become desensitized and the glucose response disappears (Van BibberKrueger et al, 2015). These results using clen buterol are in contrast to the present experiment where wholeblood glucose was decreased by feeding ZH and it was less after vs. before feeding ZH.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations